(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The purpose of this paper is to give an overview of the process of rebuilding the valuable library collection at the Institute of Art History in Zagreb due to the overlapping crises it was impacted by during 2020 (earthquake, epidemic and flood). Approach/methodology. The overall Library collection needed to be resystematized according to the UDC system from scratch since it completely collapsed due to the massive earthquake in March. This process overlapped with the primary care and conservation procedure for the personal archival paper collection of Grgo Gamulin, art historian and art critic, and the unexpected urgent need of establishing a personal archive and ex libris of our honoured colleague Academician Tonko Maroević. Findings. As a result, there is now a fully functional Library, an established ex libris of Tonko Maroević and a clean and organized paper collection of Grgo Gamulin. Originality/value. The subject of this paper gives an opportunity to gain an insight into how to deal with special types of cultural heritage under extraordinary circumstances. These simultaneous processes have sincerely and truly expanded all of our capacities, led us to create new models of collaboration between colleagues, especially with our valuable students and volunteers, and has had a significant long-term impact on rethinking our working practices and workforce development.